2011
DOI: 10.5851/kosfa.2011.31.4.557
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Physicochemical Properties of Liquid Egg during Cold Storage

Abstract: The study was performed to investigate microbial and physicochemical properties of domestic liquid eggs during cold storage. The liquid eggs used in the experiment were whole liquid, liquid egg yolks, and liquid egg whites. All samples were analyzed in summer and winter. The aerobic microorganisms were 1,270-83,300 CFU/g from non-sterilized liquid eggs produced in summer and their numbers increased from those produced in winter (ND, ~4,330 CFU/g). Total coliforms were not observed in non-sterilized whole liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Nevertheless, in raw liquid whole egg at high initial concentrations and pasteurized (70 °C for 1.5 min) liquid whole egg (regardless of the initial concentration in the latter), the growth rates of most (4/5) Salmonella strains studied here were comparable to those in egg yolk. These differences in microbial growth fitness depending on the egg fraction studied have already been demonstrated by numerous authors, such as Kang et al, who reported that Salmonella growth in egg white was slower than that in liquid egg yolk and liquid whole egg [ 23 ], and Kim et al, who demonstrated that there is a difference in Salmonella growth fitness in unpasteurized liquid eggs depending on the type of liquid egg products (liquid whole egg, egg yolk, or egg white) and storage temperature [ 11 ]. As indicated in the introduction, Salmonella growth fitness is much greater in egg yolk than in egg white because the latter has a high viscosity, an alkaline pH, and a number of antimicrobial components, including lysozyme, ovotransferrin, and several vitamin chelating proteins [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, in raw liquid whole egg at high initial concentrations and pasteurized (70 °C for 1.5 min) liquid whole egg (regardless of the initial concentration in the latter), the growth rates of most (4/5) Salmonella strains studied here were comparable to those in egg yolk. These differences in microbial growth fitness depending on the egg fraction studied have already been demonstrated by numerous authors, such as Kang et al, who reported that Salmonella growth in egg white was slower than that in liquid egg yolk and liquid whole egg [ 23 ], and Kim et al, who demonstrated that there is a difference in Salmonella growth fitness in unpasteurized liquid eggs depending on the type of liquid egg products (liquid whole egg, egg yolk, or egg white) and storage temperature [ 11 ]. As indicated in the introduction, Salmonella growth fitness is much greater in egg yolk than in egg white because the latter has a high viscosity, an alkaline pH, and a number of antimicrobial components, including lysozyme, ovotransferrin, and several vitamin chelating proteins [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 66%
“…Changes in LEW properties are complex, and mainly include sensory quality, total volatile basic nitrogen (TVB-N), pH, and albumen content, which leads to a decrease in functional properties [5]. In order to control these changes, several researchers have studied the effects of storage conditions on functional qualities, such as rheological behavior [6,7], and other physicochemical characteristics [8,9]. At present, many studies have highlighted several emerging sterilization technologies to improve microbial safety, as well as functionality and nutritionality of LEW products, such as ohmic heating [10], high hydrostatic pressure [11], and ultrahigh temperature [12].…”
Section: Introductionmentioning
confidence: 99%